2016
DOI: 10.3791/52394
|View full text |Cite
|
Sign up to set email alerts
|

A Human-machine-interface Integrating Low-cost Sensors with a Neuromuscular Electrical Stimulation System for Post-stroke Balance Rehabilitation

Abstract: A stroke is caused when an artery carrying blood from heart to an area in the brain bursts or a clot obstructs the blood flow to brain thereby preventing delivery of oxygen and nutrients. About half of the stroke survivors are left with some degree of disability. Innovative methodologies for restorative neurorehabilitation are urgently required to reduce long-term disability. The ability of the nervous system to reorganize its structure, function and connections as a response to intrinsic or extrinsic stimuli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…However, marker-based systems (e.g., VICON, UK) are too expensive for monitoring in a community setting not only in developing countries but also in developed countries including the USA. Therefore, we developed marker-less time-of-flight systems [16,26,63,64], including the low-cost (<$150) Microsoft Kinect sensor (developed for video gaming), that are increasingly used for motion capture due to its lower costs [65]. Also, postural sway based on the center of pressure (CoP) is important for balance assessment; and the Wii Balance Board (WiiBB) has demonstrated good test-retest reliability (ICC = 0.66-0.94) and construct validity when benchmarked against laboratory-grade force platforms (ICC = 0.77-0.89) [66].…”
Section: Discussionmentioning
confidence: 99%
“…However, marker-based systems (e.g., VICON, UK) are too expensive for monitoring in a community setting not only in developing countries but also in developed countries including the USA. Therefore, we developed marker-less time-of-flight systems [16,26,63,64], including the low-cost (<$150) Microsoft Kinect sensor (developed for video gaming), that are increasingly used for motion capture due to its lower costs [65]. Also, postural sway based on the center of pressure (CoP) is important for balance assessment; and the Wii Balance Board (WiiBB) has demonstrated good test-retest reliability (ICC = 0.66-0.94) and construct validity when benchmarked against laboratory-grade force platforms (ICC = 0.77-0.89) [66].…”
Section: Discussionmentioning
confidence: 99%
“…For the case of the combination of VR with FES, it is applied for the recovery of posture and body balance. This technique allows the body to be visualized on a screen by identifying the lateral deviation with respect to the central position of the body, when some type of deviation occurs, an electrical impulse is generated on the affected limb so that the person returns to its state of natural balance [10] .…”
Section: Hardware In Contextmentioning
confidence: 99%
“…In the recent years, the use of VR in stroke rehabilitation has increased, for example, Broeren et al developed VR‐based 3D games to promote motor skills and pattern of arm movements of patients suffering from left arm paresis; Holden, Saposnik et al, and Adams et al showed the importance of designing skill‐specific meaningful activities in the VR environment for rehabilitation; Sucar et al presented VR‐based Gesture Therapy platform for upper limb rehabilitation; and Ballester et al showed the efficacy of the VR‐based intervention in enhancing motor skills of the paretic limb in hemiparetic stroke patients. Also, researchers have used VR in conjunction with external peripherals, for example, Wii (Nintendo), Kinect Sensor (Microsoft), and haptic devices, which add to delivering a feeling of immersion in the task environment, thereby making the task motivating.…”
Section: Introductionmentioning
confidence: 99%